Biodiversity of Zooplanktons in Al-Razzaza Lake at Karbala Province/ Iraq - Sh., Fawzi; N.Hashim, Neam; M. Al-Taee, Mayson; Abd Naima, Zahraa (Al-Qadisiyah Journal of Pure Science, 2018)
This study was conducted to assess the biodiversity of zooplanktons with assessing the water quality of Al-Razzaza Lake by chemical and physical analysis in addition to The Shannon – Wiener biological diversity index. The samples were collected each month from January 2013 to March 2014, from three sits. The chemical and physical analysis includes: water temperature, DO, salinity, TSS & pH. The rotifers that collected during the study period were consisting of seven species, including: Keratellaquadrata; Keratellatropica; Branchionusquadridentata; Branchionus urceolaris; Cephalodellatantilliodes; Notholcasquamula and Synchaetatremula. Arthropods recorded in the present study were Crustacea and Hexapoda (Insects). Crustacea consist of microfauna (zooplanktons) that include Copepoda (Cyclope spp. &Diaptomus spp.) and Cladocera (Diaphanosomabrachyrum). The Shannon – Wiener biological diversity index had the lowest value at 0.85 in winter 2013at site 3, while the highest value was 2.0 in autumn at site 1, for zooplanktons.